2004
DOI: 10.1161/01.str.0000140891.70547.56
|View full text |Cite
|
Sign up to set email alerts
|

Findings From the Reanalysis of the NINDS Tissue Plasminogen Activator for Acute Ischemic Stroke Treatment Trial

Abstract: Background and Purpose-Following publication of concerns about the results of the National Institute of NeurologicalDisorders and Stroke (NINDS) intravenous tissue plasminogen activator (t-PA) in acute stroke treatment trial, NINDS commissioned an independent committee "to address whether there is concern that eligible stroke patients may not benefit from t-PA given according to the protocol used in the trials and, whether the subgroup imbalance (in baseline stroke severity) invalidates the entire trial." Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
165
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(179 citation statements)
references
References 35 publications
7
165
1
6
Order By: Relevance
“…3 Similar to the National Institute of Neurological Diseases and Stroke analysis, this made no difference and the results remain clearly and undeniably positive. 4 Intriguingly, although the link between time and treatment effect is further confirmed by these results, there was no increase in the rate of symptomatic intracerebral hemorrhage beyond 3 hours using a variety of different definitions. The rate was essentially the same as the National Institute of Neurological Diseases and Stroke trial at 7% using the conservative National Institute of Neurological Diseases and Stroke definition.…”
mentioning
confidence: 62%
“…3 Similar to the National Institute of Neurological Diseases and Stroke analysis, this made no difference and the results remain clearly and undeniably positive. 4 Intriguingly, although the link between time and treatment effect is further confirmed by these results, there was no increase in the rate of symptomatic intracerebral hemorrhage beyond 3 hours using a variety of different definitions. The rate was essentially the same as the National Institute of Neurological Diseases and Stroke trial at 7% using the conservative National Institute of Neurological Diseases and Stroke definition.…”
mentioning
confidence: 62%
“…6 Two groups re-analysed the NINDS data adjusting for baseline differences, with different conclusions. 7,8 Furthermore, care in a multidisciplinary stroke unit is the only proven therapy to date, with a reduction in death and disability equivalent to that claimed by thrombolysis. 9 IST-3 was the only trial to control for this variable, and it is plausible that some of the benefits seen in NINDS and ECASS-III were due to variability in level of care.…”
mentioning
confidence: 99%
“…At the same time, a smaller study, the Alteplase Thrombolysis for Acute Noninterventional Therapy in Ischemic Stroke (ATLANTIS) study tested delayed (3-to 5-h) administration of alteplase, but it was negative. Independent re-analysis of the NINDS data [52], and a pooled analysis of all patients in all of these 4 trials confirmed the positive effect of t-PA and demonstrated the importance of treating patients as early in the course of their infarction as possible [53]. The odds ratio of a favorable 3-month outcome increased as the onset to treatment time decreased (p=0.005).…”
Section: Review Of Phase 3 Efficacy Trialsmentioning
confidence: 87%